2010
DOI: 10.1186/1471-2156-11-10
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense mutation in the beta-carotene oxygenase 2 (BCO2) gene is tightly associated with accumulation of carotenoids in adipose tissue in sheep (Ovis aries)

Abstract: BackgroundSheep carcasses with yellow fat are sporadically observed at Norwegian slaughter houses. This phenomenon is known to be inherited as a recessive trait, and is caused by accumulation of carotenoids in adipose tissue. Two enzymes are known to be important in carotenoid degradation in mammals, and are therefore potential candidate genes for this trait. These are beta-carotene 15,15'-monooxygenase 1 (BCMO1) and the beta-carotene oxygenase 2 (BCO2).ResultsIn the present study the coding region of the BCMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 18 publications
(26 reference statements)
4
87
1
2
Order By: Relevance
“…These enzymes play an important role in carotenoid homeostasis of blood and tissues, as seen by genetic variability in the corresponding genes in humans and animals (35)(36)(37)(38)(39). However, little is known as to whether an additional mechanism exists in cells to chemically modify these lipids.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes play an important role in carotenoid homeostasis of blood and tissues, as seen by genetic variability in the corresponding genes in humans and animals (35)(36)(37)(38)(39). However, little is known as to whether an additional mechanism exists in cells to chemically modify these lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Although these proteins may be required for the uptake and stabilization of these compounds in the human retina, they are not sufficient to explain why xanthophylls are not found in other mammalian retinas, because these binding proteins are often found in these animals' retinas, too. Recent investigations on various mammalian BCO2 enzymes have shown that BCO2 can generally cleave xanthophylls such as lutein and zeaxanthin, and BCO2 mutations can cause the tissues of chickens, cows, and sheep to develop a deep yellow color due to carotenoid deposition (13)(14)(15)(16)(17). To explain the unique deposition of xanthophyll carotenoids in the primate retina, we hypothesized that either human BCO2 is not expressed in human retina, or it is an inactive carotenoid cleavage enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Its physiological function is supported by genetic evidence from several species. A nonsense mutation in the sheep BCO2 gene that introduces a stop codon at amino acid 66 of the 575-aa full-length protein is strongly associated with a yellow fat phenotype due to the high amount of lutein that deposits in tissue (15). Cis-acting and tissue-specific regulatory mutations that inhibit the expression of BCO2 in domestic chickens can cause them to have yellow skin secondary to carotenoid accumulation (16).…”
mentioning
confidence: 99%
“…A nonsense mutation (c.196C>T) of the BCDO2 gene was also found to be strongly associated with yellow fat in sheep (Våge DI & Boman IA, 2010).…”
Section: Introductionmentioning
confidence: 95%